Verticalização e modernidade: São Paulo 1940-1957 - Okano, Tais Lie (2007)
The present work discusses the vertical growth in São Paulo and the constitution of Modernity. The analysis has focus in the period of 1940 and 1957, entering many aspects: economics, politics, culturals and suitable legislations to the process of the city vertical growth. This process contributed for the establishment of the metropolis, certifying the technological and productive capacity to it, the intensity of the industrial activity. Through the system organization and the analysis of this work studied object, the part of the buildings constructed with elevator between 1940 and 1957, three sub periods in the São Paulo vertical growth were characterized in the transition from eclectic buildings till modern architecture which will dominate after the 50s.